Influence of electronically conductive additives on the cycling performance of argyrodite-based all-solid-state batteries. Issue 2 (7th January 2020) - Strauss, Florian; Stepien, Dominik; Maibach, Julia; Pfaffmann, Lukas; Indris, Sylvio; Hartmann, Pascal; Brezesinski, Torsten
Abstract : Low-surface-area carbon black helps to improve the performance of bulk-type all-solid-state batteries using NCM622 cathode material and argyrodite Li6 PS5 Cl solid electrolyte. Abstract : All-solid-state batteries (SSBs) are attracting widespread attention as next-generation energy storage devices, potentially offering increased power and energy densities and better safety than liquid electrolyte-based Li-ion batteries. Significant research efforts are currently underway to develop stable and high-performance bulk-type SSB cells by optimizing the cathode microstructure and composition, among others. Electronically conductive additives in the positive electrode may have a positive or negative impact on cyclability. Herein, it is shown that for high-loading (pelletized) SSB cells using both a size- and surface-tailored Ni-rich layered oxide cathode material and a lithium thiophosphate solid electrolyte, the cycling performance is best when low-surface-area carbon black is introduced.